Bioorthogonal Cleavage and Exchange of Major Histocompatibility Complex Ligands by Employing Azobenzene‐Containing Peptides1. Issue 49 (27th October 2014) - Choo, Joanna A. L.; Thong, Sock Yue; Yap, Jiawei; van Esch, Wim J. E.; Raida, Manfred; Meijers, Rob; Lescar, Julien; Verhelst, Steven H. L.; Grotenbreg, Gijsbert M.
Abstract Bioorthogonal cleavable linkers are attractive building blocks for compounds that can be manipulated to study biological and cellular processes. Sodium dithionite sensitive azobenzene‐containing (Abc) peptides were applied for the temporary stabilization of recombinant MHC complexes, which can then be employed to generate libraries of MHC tetramers after exchange with a novel epitope. This technology represents an important tool for high‐throughput studies of disease‐specific T cell responses.